Time Series InSAR Monitoring and Analysis of Spatiotemporal Evolution Characteristics of Land deformation in Typical Artificial Islands around Hainan Island - Shusu Duan; Haixiang Huang; Zhi Zhou; XueXin Yang; Xin Yang; Weihua Wang; Xiaoxiang Chen (Tehnički Vjesnik, 2025)
This study systematically investigated the spatiotemporal dynamics and underlying mechanisms of land deformation across three artificial islands in Hainan Province, China-Ocean Flower Island, Bright Pearl Island, and Wanning Sun Island, which adopts 29 Sentinel-1A ascending orbit SAR images acquired between May 2017 and June 2024. By integrating time series InSAR techniques (PS-InSAR and SBAS-InSAR) with leveling validation, we evaluated deformation trends and causative drivers through historical satellite imagery and sea level datasets to advance settlement monitoring methodologies. Key findings demonstrate the following relationships. (1) Strong agreement between PS-InSAR and SBAS-InSAR outputs in spatial deformation patterns and magnitudes, validating their utility for artificial islands stability assessment. (2) Distinct patterns of spatial and temporal evolution characterize settlement: rapid initial settlement during intensive construction phases (construction impact), followed by deceleration and eventual stabilization, with spatial hotspots localized in engineered zones. Anthropogenic activities amplify settlement rates compared to natural consolidation processes. (3) Differential marine hydrodynamics impacts are observed: Ocean Flower and Bright Pearl Islands display seaward-increasing settlement gradients correlated with wave energy distribution and seasonal sea level variations. In contrast, Wanning Sun Island’s composite caisson-retaining wall system minimizes hydrodynamic disturbances, highlighting the role of structural engineering in mitigating marine hydrodynamics effects. The study establishes that artificial islands stability is governed by synergistic interactions among construction impact, coastal engineering design, and marine environmental forcing. These findings advance time series InSAR-based settlement monitoring frameworks and provide critical insights for optimizing disaster resilience in coastal reclamation projects, emphasizing the importance of integrating patterns of spatial and temporal evolution into urbanized island ecosystem management.